Perinatal care and monitoring strategies for women with mental health disorders: an integrative review (Revista Contexto & Saúde, 2025)
Objective: To analyze the evidence available in the literature on strategies and challenges in prenatal care for pregnant women with mental disorders. Methodology: Integrative review of the literature published between 2013 and 2023 using the BVS, MEDLINE®, Scopus, and Web of Science databases. Results and discussion: Twenty-one articles were selected. The critical analysis of their contents revealed three categories for discussion: the perceptions and accounts of women with mental disorders about prenatal care; health workers’ experiences of and knowledge about mental health during pregnancy; and strategies and interventions for mental health during prenatal care. Conclusion: The results demonstrated the importance of more discussions about the prenatal care needs of women with mental disorders. These women should be included and listened to in discussions about the delivery of such care. The approach should involve having adequately trained, inclusive multidisciplinary teams to deliver effective, comprehensive care and support.
Keywords: Women's health; Mental health; Prenatal care; Mental disorders